ANALISIS PENGETAHUAN DAN KRITERIA PEMILIHAN BANK SYARIAH - ANNA SARDIANA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
This study aims to analyze the selection criteria considered by students in choosing a Sharia bank; know the level of student knowledge of Islamic banking products; and analyzing consumer attitudes towards Islamic banks. The research subjects were students who used the services of Islamic banks or those who did not use Islamic banks in Jakarta. Data analysis methods are statistical descriptive and factor analysis. The analysis concluded that there were six factors that were considered by students in choosing a Sharia bank, including: perception and process, physical condition, price, human resources, relationships and location factors. Consumer perception is the most influential factor on consumer decisions in choosing a Sharia bank. In general, the majority of respondents have limited knowledge about Islamic banking. Religion is not the main reason for students to choose a Sharia bank. Students consider Sharia bank service friendliness more than other factors.